System for Development of Local Work Unit Budget Work Plan (RKA-SKPD) at the Housing Office the People and Settlement Area of Gorontalo Province - Dian Fitriani Karim; Nuzlan Botutihe; Ismail Ayuba (Journal of Management and Administration Provision, 2021)
This study aims to determine the System for Formulating Regional Work Unit Budget Plans (RKA-SKPD) in the Public Housing and Settlement Areas of Gorontalo Province. The research method used is a qualitative approach with descriptive research type. The results showed that in the preparation of the RKA- SKPD it was found that there were problems in its preparation. These problems are the lack of planning documents in the preparation of the RKA, budget constraints resulting in reduced budgets in program implementation, frequent delays in preparation time, copy and paste over the previous year's budget, lack of enthusiasm for budget efficiency and many other problems.